Study on lubrication effect on motorbike chain transmissions. Issue 5 (8th August 2016) - Palazzetti, Roberto; Yan, Xiu-Tian
Abstract : Purpose: This paper reports on the findings of first of its kind to examine motorbike's chain transmission, focusing on chain lubrication and its effect on the temperature, efficiency and vibrations of the transmission. The novelty of the paper is to investigate holistically the lubrication effect on the transmission by comparing its dynamic performances under three different lubrication conditions: chain not lubricated at all, chain lubricated with a spray polytetrafluoroethylene (PTFE) addicted lube and chain lubricated with a mineral oil at every minute of the test. Design/methodology/approach: A novel mechatronic test rig has been designed and manufactured using a thermocamera, a dynamometer and an accelerometer respectively. The rig enables a multi-parameter dynamic and real-time sensing investigation of any motorbike chain system by recording temperature, transmission's efficiency and vibrations for any tests by. An experimental investigation has been conducted by running a chain under three aforementioned lube conditions at different speeds with the purposes of: (A) measuring the effect that each lube condition has on three critical parameters: temperature, vibrations and the efficiency of the transmission, and (B) identify the best conditions for practical use. Findings: Results showed that proper use of lubricant can increase the efficiency of the system, by an estimated average of 4.1% is desirable. Additionally, using a continuous lubrication with a mineral oil lubricant leads to better transmission compared to the use of the spray PTFE from the efficiency and thermal points of view. Originality/value: This work presents an experimental investigation on the effect of two different kinds of lubrication form motorbike chain on transmission's efficiency. The findings are still valid for different applications of chain transmission in dirty environments. Novelty of the paper is highlighted as follows: this is the first work scientifically investigating the importance of lubrication on chain in harsh environments, particularly of motorbike chain. The work reports a comprehensive lete set experiments and analysis of thermal and mechanical effect because of the presence of lubricant has never been shown. Three kinds of lubricants have been used, and show their distinctive effects which are separately highlighted.